Analisis Konflik Sosial Dalam Cerpen “Panggung Terakhir” Karya M Rosyid HW - Desta Ramadani Fitri (Concept: Journal of Social Humanities and Education, 2024)
Social conflict usually occurs because competition in the economic field, such as competition for resources or jobs, can cause conflict between competing groups. This research explains the forms, causes and impacts in the short story "Last Stage" by M Rasyid Hw. The objectives of this research are: (1) Describe the form of social conflict; (2) analyzing the causes of social conflict; and (3) explain the negative and positive impacts of social conflict. This research method uses qualitative descriptive methods and literature. The primary data source is the short story "Last Stage" and secondary data sources are articles and theoretical books. Data collection techniques use reading and note-taking techniques. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of this research are (1) a picture of social conflict in the form of arrogance, arrogance and nepotism; (2) the causes of social conflict are differences in individual character and differences in interests; (3) the negative impact of social conflict can lead to being hated by someone, the division of society, and a struggle for power.